Knockdown of DIAPH3 Inhibits the Proliferation of Cervical Cancer Cells through Inactivating mTOR Signaling Pathway. (6th October 2021) - Wan, Linling; Zhu, Jiamin; Wu, Qunying
Abstract : Cervical cancer (CC) ranks fourth for both incidence and mortality among females in worldwide. Therefore, it is urgent to explore new therapeutic and diagnostic targets for cervical cancer. Diaphanous-related formin 3 (DIAPH3) has been identified to play crucial roles in many malignant tumors. But its function and potential mechanism in CC remain largely unknown. In our study, DIAPH3 was frequently upregulated in CC tissue samples and increased expression of DIAPH3 was associated with poor overall survival according to several databases. Through in vitro and in vivo experiments, we found that decreased expression levels of DIAPH3 significantly inhibited the progression of CC. The GSEA analysis and western blot assay indicated that DIAPH3 was associated with the mTOR signaling pathway. The univariate and multivariate Cox analysis indicated that DIAPH3 was an independent prognosis risk factor in TCGA-CESC. And we confirmed that DIAPH3 expression was clearly related to tumor immune infiltrating cells (TIICs) by the analysis of CIBERSORT and TIMER databases. Taken together, we revealed that DIAPH3 plays as an oncogene through mTOR signaling pathway and DIAPH3 might be a potential prognostic biomarker in CC.